Avicenna and the Aristotelian tradition - Gutas, Dimitri, 1945- (Leiden ; Boston)
xxxi, 617 s.
Keywords: "Through close study of Avicenna's statements and major works, Dimitri Gutas traces Avicenna's own sense of his place in the Aristotelian tradition and the history of philosophy in Islam, and provides an introduction to reading his philosophical works by delineating the approach most consistent with Avicenna's intention and purpose in philosophy. The second edition of this foundational work, which has quickened fruitful research into the philosopher in the last quarter century, is completely revised and updated, and adds a new final chapter summarizing Avicenna's philosophical project. It is also enlarged with the addition of a new appendix which offers a critical inventory of Avicenna's authentic works, updating the work of Mahdavi (1954) with additional information on all manuscripts and important editions and translations. Its usefulness enhanced, the book provides primary orientation to Avicenna's philosophy and works and constitutes an indispensable research tool for their study." --